ANALYSIS OF KNOWLEDGE ON CHRONIC OBSTRUCTIVE LUNG DISEASE - Susanthy Djajalaksana; Aditya Sri Listyoko; Maria Kristiani; Tiar Oktavian Effendi; Magdalena Sirait (Journal of Community Health and Preventive Medicine, 2022)
ABSTRAKBackground : Chronic obstructive pulmonary diseaseÂ (COPD) is a leading cause of morbidity, mortality and disability worldwide and represents a huge economical burden for the healthcare system. By knowing the level of public understanding of this disease, we were able to find out what education could be given to increase understanding about COPD. The aim of this study was to determine the level of knowledge of the non-medical and medical personnel about COPD.Methods : This is descriptive research. The research was conducted cross-sectionally with 200 respondents consisting of 100 medical subjects and 100 non-medical subjects. This research was carried out in the RSSA environment in November 2021. The data collection technique is that respondents filled out a Google Form.Results : The total score of the six categories showed that 73.875% of the medical group and 47.17% of the non-medical group already understood COPD. In all categories, the results of the analysis showing statistical significance (p<0.001).Conclusion : Our study shows significant knowledge about all knowledge of COPD between the general public and medical personnel.Suggestion : socialization to the public about COPD and the importance of the community getting to know COPD in preventive and treatment measures.Â Keywords: COPD, education, questionnaireÂ